Analisis Kritis Isu-Isu Pendidikan Islam Dalam Kompetisi Negara Asean (Studi Kasus Di Indonesia, Brunei Darussalam Dan Malaysia) - Dwi Listiani; Fitri Ariyanto; Sukari (4, 2024)
The three countries of Indonesia, Brunei Darussalam, and Malaysia have unique histories and developments in Islamic education, facing various challenges and opportunities in the context of modernization and globalization. This analysis is conducted by examining the structure and curriculum of Islamic education, government policies, and the main issues faced by each country. In Indonesia, the main challenges include the quality of education, accessibility, and integration with the national education system. In Brunei Darussalam, the primary focus is on resource limitations and curriculum modernization. Meanwhile, in Malaysia, the dualism of the education system, political influences, and teacher quality are the main concerns. This research aims to critically analyze the issues of Islamic education in three ASEAN countries: Indonesia, Brunei Darussalam, and Malaysia. Through comparison and critical analysis, this research finds that cultural factors, government policies, and regional competition significantly influence the form and effectiveness of Islamic education in these three countries. Additionally, this research highlights the positive and negative impacts of competition in the Islamic education sector in ASEAN and provides policy recommendations that can improve the quality and accessibility of Islamic education regionally. The results of this research are expected to provide insights for policymakers, educators, and researchers in developing more effective and sustainable strategies for Islamic education in ASEAN.. Abstrak Ketiga negara Indonesia, Brunei Darussalam dan Malaysia ini memiliki sejarah dan perkembangan pendidikan Islam yang unik serta menghadapi berbagai tantangan dan peluang dalam konteks modernisasi dan globalisasi. Analisis ini dilakukan dengan menelaah struktur dan kurikulum pendidikan Islam, kebijakan pemerintah, serta isu-isu utama yang dihadapi masing-masing negara. Di Indonesia, tantangan utama termasuk kualitas pendidikan, aksesibilitas, dan integrasi dengan sistem pendidikan nasional. Di Brunei Darussalam, keterbatasan sumber daya dan modernisasi kurikulum menjadi fokus utama. Sementara itu, di Malaysia, dualisme sistem pendidikan, pengaruh politik, dan kualitas guru menjadi perhatian utama. Penelitian ini bertujuan untuk menganalisis secara kritis isu-isu pendidikan Islam di tiga negara ASEAN: Indonesia, Brunei Darussalam, dan Malaysia. Melalui perbandingan dan analisis kritis, penelitian ini menemukan bahwa faktor budaya, kebijakan pemerintah, dan kompetisi regional sangat mempengaruhi bentuk dan efektivitas pendidikan Islam di ketiga negara. Selain itu, penelitian ini menyoroti dampak positif dan negatif dari kompetisi dalam sektor pendidikan Islam di ASEAN, serta memberikan rekomendasi kebijakan yang dapat meningkatkan kualitas dan aksesibilitas pendidikan Islam secara regional. Hasil penelitian ini diharapkan dapat memberikan wawasan bagi pembuat kebijakan, pendidik, dan peneliti dalam mengembangkan strategi yang lebih efektif dan berkelanjutan untuk pendidikan Islam di ASEAN